HR Marketing - Employer Brand Capturing, retaining and captivating talent - IBN MAJDOUB HASSANI , Mohammed Aimane; AKESBI, Meryem (Revue Internationale des Sciences de Gestion, 2021)
Today, companies are facing a wide range of changes, whether economic, technological, environmental or sociological. As a result, they are about to enter a period of radical transition, which will result in a serious decline in the labour force and, by the same token, in the available workforce (Légaré, 2004). This will have a radical impact on the labour market. Not only will the workforce be scarcer, older and more diversified, but it will also be more demanding and more difficult to retain (Fabi et al., 2009). In recent years, many employers in the private and parapublic sectors have begun to reflect on the strategies to be implemented in order to mobilize and retain their human resources (HR). In this article, we mobilize the literature on HR practices, from human resources retention to the concept of employer branding, while taking into account the constantly changing socio-economic context. The objective is thus to arrive at a conceptual model of employer branding practices.